Cranial Chordoma: A New Preoperative Grading System. Issue 3 (3rd November 2017) - Brito da Silva, Harley; Straus, David; Barber, Jason K; Rostomily, Robert C; Ferreira, Manuel; Sekhar, Laligam N
Abstract: BACKGROUND: Chordomas are rare but challenging neoplasms involving the skull base. A preoperative grading system will be useful to identify both areas for treatment and risk factors, and correlate to the degree of resection, complications, and recurrence. OBJECTIVE: To propose a new grading system for cranial chordomas designed by the senior author. Its purpose is to enable comparison of different tumors with a similar pathology to clivus chordoma, and statistically correlate with postoperative outcomes. METHODS: The numerical grading system included tumor size, site of the tumor, vascular encasement, intradural extension, brainstem invasion, and recurrence of the tumor either after surgery or radiotherapy with a range of 2 to 25 points; it was used in 42 patients with cranial chordoma. The grading system was correlated with number of operations for resection, degree of resection, number and type of complications, recurrence, and survival. RESULTS: We found 3 groups: low-risk 0 to 7 points, intermediate-risk 8 to 12 points, and high-risk ≥13 points in the grading system. The 3 groups were correlated with the following: extent of resection (partial, subtotal, or complete; P < .002); number of operative stages to achieve removal ( P < .014); tumor recurrence ( P = .03); postoperative Karnofsky Performance Status ( P < .001); and with successful outcome ( P = .005). The grading system itself correlated with the outcome ( P = .005). CONCLUSION: The proposed chordoma grading system can help surgeons to predict the difficulty of the case and know which areas of the skull base will need attention to plan further therapy.